2008
DOI: 10.1021/ie800142d
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Membranes by Layer-By-Layer Assembly of Polyelectrolytes and In Situ Polymerization of Acrylic Acid for Applications in Enzymatic Catalysis

Abstract: This research work was directed toward the development of highly active, stable, and reusable functionalized polymeric membrane domains for enzymatic catalysis. Functionalized membranes were created by two different approaches. In the first approach, which involved alternative attachment of cationic and anionic polyelectrolytes, functionalization was performed using a layerby-layer (LBL) assembly technique within a nylon-based microfiltration (MF) membrane. In the second approach, a hydrophobic polyvinylidene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 85 publications
3
36
0
Order By: Relevance
“…4). Previous work has shown that immobilization of enzymes via electrostatic interaction provides stability comparable to covalent attachment, yet maintains high activity more characteristic of the enzyme in solution (26). Although this PVDF-based system is suitable for the generation of H 2 O 2 , here, we demonstrate how another readily available supporting material, regenerated cellulose (RC), can be functionalized and used for the same purpose (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…4). Previous work has shown that immobilization of enzymes via electrostatic interaction provides stability comparable to covalent attachment, yet maintains high activity more characteristic of the enzyme in solution (26). Although this PVDF-based system is suitable for the generation of H 2 O 2 , here, we demonstrate how another readily available supporting material, regenerated cellulose (RC), can be functionalized and used for the same purpose (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…A key challenge for the plasma treatment process is aging as a result of post-plasma oxidation initiated by the reaction between remaining radicals and in-diffusing atmospheric oxygen as well as the movement of some of the polymer chains from the surface into the bulk [15]. Recently, adsorption of enzymes on polyelectrolyte-modified membrane surfaces has emerged as a versatile, gentle and easy method for immobilization [16][17][18][19][20][21] which occurs mainly via ionic binding of enzyme molecules to the charged surface. The adsorption process can be conducted in an aqueous solution under mild conditions which minimize the loss of enzyme activity.…”
Section: Introductionmentioning
confidence: 99%
“…The strengthening of immobilization would be easily archived by employing another immobilizing method; covalent bonding [15][16][17][18][19][20][21][22][23] There are some solutions used to improve the stability of enzyme membranes. To prevent the fouling of the membranes (protein adhesion), the surface morphology of the materials is important.…”
Section: Introductionmentioning
confidence: 99%